PROBLEMATIKA LEARNING LOSS PASCA-PANDEMI DAN TANTANGAN PEMULIHAN PENDIDIKAN - Talitha Salsabila (Journal of Education and Learning, 2025)
The COVID-19 pandemic has had a significant impact on the global education system, including in Indonesia, with the emergence of the phenomenon of learning loss, which has led to a decline in academic achievement and a widening educational gap. During distance learning, limited access to technology, low digital literacy, and socioeconomic inequality have worsened the quality of learning and student participation. This study aims to analyze the factors causing post-pandemic learning loss, its impact on the national education system, and the challenges faced in learning recovery efforts. The research method used is descriptive qualitative, with a literature study approach through content analysis of various scientific sources and reports from international institutions from 2020–2024. The results indicate that learning loss is caused by structural, pedagogical, and psychosocial factors such as limited online learning tools, low teacher and parental preparedness, and decreased student motivation and mental health. The impacts include decreased learning outcomes, weakened basic skills, emotional disturbances, and widening educational inequality. The main challenges to educational recovery include the heterogeneity of student abilities, the need for curriculum simplification, limited teacher resources, and strengthening socio-emotional support. Recovery efforts require cross-sector collaboration and sustainable policies to mitigate the long-term impact on human resource quality.